2022
DOI: 10.3390/w14182933
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis of Numerical Simulation of Seawater Intrusion Using Deep Learning-Based Surrogate Model

Tiansheng Miao,
He Huang,
Jiayuan Guo
et al.

Abstract: Seawater intrusion is expected to cause a shortage of freshwater resources in coastal areas which will hinder regional economic and social development. The consequences of global climate change include rising sea levels, which also affect the results of the predictions of seawater intrusion that are based on simulations. It is thus important to examine the impact of the randomness in the rise in sea levels on the uncertainty in the results of numerical simulations that are used to predict seawater intrusion. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In recent years, several surrogate model approaches have been suggested to approximate simulation models for uncertainty analysis, such as Polynomial Chaos Expansion (PCE); Gaussian Process Emulation (GPE) [41]; Gaussian processes [42]; Kriging [26,43,44]; Radial Basis Function (RBF) [45]; Support Vector Regression (SVR) [46]; Artificial Neural Network (ANN) [47]; Multi-gene Genetic programming (MGGP) [48]; Kernel Extreme Learning Machine (KELM) [49]; a hybrid approach using the Multilevel Monte Carlo method (MLMC); a graph convolutional neural network and a feed-forward neural network [50]; and a Deep Belief Neural Network (DBNN) [51]. While earlier studies have demonstrated certain achievements, the application of surrogate models encounters challenges related to scalability and accuracy, particularly in scenarios where contaminantrelated associations exhibits pronounced non-linearity or high dimensionality [52].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several surrogate model approaches have been suggested to approximate simulation models for uncertainty analysis, such as Polynomial Chaos Expansion (PCE); Gaussian Process Emulation (GPE) [41]; Gaussian processes [42]; Kriging [26,43,44]; Radial Basis Function (RBF) [45]; Support Vector Regression (SVR) [46]; Artificial Neural Network (ANN) [47]; Multi-gene Genetic programming (MGGP) [48]; Kernel Extreme Learning Machine (KELM) [49]; a hybrid approach using the Multilevel Monte Carlo method (MLMC); a graph convolutional neural network and a feed-forward neural network [50]; and a Deep Belief Neural Network (DBNN) [51]. While earlier studies have demonstrated certain achievements, the application of surrogate models encounters challenges related to scalability and accuracy, particularly in scenarios where contaminantrelated associations exhibits pronounced non-linearity or high dimensionality [52].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Piper diagrams, Gibbs plots, ion ratios, and saturation indices play a significant role in studying the hydrogeochemical controlling mechanisms [35][36][37][38][39][40]. In addition, numerical simulation methods can be used to evaluate the exchange of groundwater with seawater and the transport characteristics of nutrients [41][42][43][44]. Water quality indices (WQIs), machine learning, and the partial least squares regression model (PLSR) are typically used to evaluate the pollution level in groundwater [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…A fuzzy system is the first stage in building a network of fuzzy systems and can be created by "if-then" rules. The mathematical techniques are known as the recurrent network (RN), time-lagged recurrent network (TLRN), ANN, and ANFIS are directly derived from the workings of the human brain [30]. These methods are promising for simulating response variables and can also be used with nonlinear systems due to their simplicity.…”
Section: Introductionmentioning
confidence: 99%